Credit Rating Agencies in Emerging Democracies : Guardians of Fiscal Discipline? - Hanusch, Marek; Vaaler, Paul M. (World Bank, Washington, DC, 2013)
Credit rating agencies have drawn criticism for failing to anticipate and deter root causes of the 2008-2009 financial crisis in the United States. However, this paper presents evidence that credit rating agencies regularly anticipate and deter governments in emerging democracies from opportunistic borrowing and potential financial crises related to elections and the political budget cycle behavior they encourage. The paper considers a sample of 18 such countries holding 32 presidential elections from 1989 to 2004. The analysis shows that credit rating agencies induced greater fiscal discipline during election periods when governments had incentives to borrow opportunistically for short-term electoral gain. Countries with higher credit rating agency sovereign ratings borrowed less than lower-rated countries in election periods, but borrowed more in non-election periods. Credit rating agencies promoted fiscal discipline during increasingly frequent election periods in emerging democracies.